2013
DOI: 10.1007/s00414-013-0845-4
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal age determination of the hand: a comparison of methods

Abstract: Until final completion of maturation processes at the age of approximately 18 years, determination of the skeletal age of the hand plays a central role in forensic age diagnostics in living persons in criminal proceedings. In this process, assessment of hand radiographs relies primarily on the stage of development of the epiphyseal nuclei, the increase in size of the individual bones and of the hand skeleton as a whole, changes in the shape of the various skeletal elements and ossification of the epiphyseal pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 24 publications
0
17
0
2
Order By: Relevance
“…In fact, numerous studies have demonstrated that, after the adolescent period, age estimation is increasingly more difficult, as changes in the carpal bones are less readily discernable after 14-16 years of age [45]. Mineralization of the carpal bones begins at birth and lasts until approximately 13-14 years of age for girls and 15-16 years of age for boys; mineralization of the epiphyses of the ulna and radius continues until 16-17 years of age [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, numerous studies have demonstrated that, after the adolescent period, age estimation is increasingly more difficult, as changes in the carpal bones are less readily discernable after 14-16 years of age [45]. Mineralization of the carpal bones begins at birth and lasts until approximately 13-14 years of age for girls and 15-16 years of age for boys; mineralization of the epiphyses of the ulna and radius continues until 16-17 years of age [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently employed method of bone age calculation is the Greulich &Pyle Atlas (16)(17)(18)(19). This atlas is a qualitative method using reference radiographic images of the left error which never exceeds 1 year for the 95% confidence interval.…”
Section: Resultsmentioning
confidence: 99%
“…The other issue, in forensic practice, is the importance of an accurate assessment of skeletal age [43] in all age groups, due to the fact that it may determine the future of young In all the aforementioned circumstances in which age assessment analysis for forensic purposes is required, the results can have very important consequences for individuals, as the aim is to determine if they should be assigned to childhood or adulthood. Inaccuracy in age estimation can negate an adult access to freedom.…”
Section: Discussionmentioning
confidence: 99%